PENGARUH BRANDING INFLUENCER, DIGITAL MARKETING DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SKINCARE HANASUI - Nurjanah; Ageng Putri Yusnanda; Eni Haryani Bahri; Hamzah Zainuri; Abdul Hamid (Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2026)
The growing competition within the local skincare industry in Indonesia, which encourages companies to optimize marketing strategies through influencers, digital marketing, and product quality improvements to influence consumer purchase intention. This study aims to analyze the influence of Branding Influencers, Digital Marketing, and Product Quality on Purchase Intention for Hanasui skincare products, both partially and simultaneously. The research employs a quantitative approach using a survey method through questionnaires distributed to 96 respondents who were aware of or had used Hanasui skincare products. The sampling technique used was purposive sampling, while data analysis was conducted through validity and reliability tests, t-test, F-test, multiple linear regression analysis, and the coefficient of determination (Adjusted R²). The t-test results show that partially, the Branding Influencer variable has a positive and significant effect on purchase intention with a t-value of 2.061 > 1.661 and a significance level of 0.042 < 0.05; Digital Marketing has a positive and significant effect with a t-value of 4.187 > 1.661 and a significance level of 0.000 < 0.05; and Product Quality has a positive and significant effect with a t-value of 4.950 > 1.661 and a significance level of 0.000 < 0.05. Furthermore, the F-test results indicate that the three variables simultaneously have a significant effect on Purchase Intention with an F-value of 176.883 > 2.47 and a significance level of 0.000 < 0.05. The Adjusted R Square value of 0.847 indicates that the three variables explain 84.7% of the variation in Purchase Intention, while the remaining 15.3% is influenced by other factors outside the scope of this study.